2022
DOI: 10.3390/ijms23105660
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Physiological Analyses of a Navel Orange Mutant with Improved Drought Tolerance and Water Use Efficiency Caused by Increases of Cuticular Wax Accumulation and ROS Scavenging Capacity

Abstract: Drought is one of the main abiotic stresses limiting the quality and yield of citrus. Cuticular waxes play an important role in regulating plant drought tolerance and water use efficiency (WUE). However, the contribution of cuticular waxes to drought tolerance, WUE and the underlying molecular mechanism is still largely unknown in citrus. ‘Longhuihong’ (MT) is a bud mutant of ‘Newhall’ navel orange with curly and bright leaves. In this study, significant increases in the amounts of total waxes and aliphatic wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 103 publications
(121 reference statements)
0
3
0
Order By: Relevance
“…Drought is the main environmental stress that limits citrus growth and reduces its fruit quality and economic value (Rodríguez-Gamir et al, 2010 ). Our recent report revealed that cuticular waxes play an important role in limiting citrus non-stomatal water loss and regulating the citrus response to drought stress (Liang et al, 2022 ). However, the underlying molecular mechanism, especially the contribution of specific wax biosynthesis gene to drought tolerance is still unclear in citrus.…”
Section: Discussionmentioning
confidence: 99%
“…Drought is the main environmental stress that limits citrus growth and reduces its fruit quality and economic value (Rodríguez-Gamir et al, 2010 ). Our recent report revealed that cuticular waxes play an important role in limiting citrus non-stomatal water loss and regulating the citrus response to drought stress (Liang et al, 2022 ). However, the underlying molecular mechanism, especially the contribution of specific wax biosynthesis gene to drought tolerance is still unclear in citrus.…”
Section: Discussionmentioning
confidence: 99%
“…Histochemical staining of NBT and DAB was used to monitor the O 2− - and H 2 O 2 accumulation, respectively, in Arabidopsis and lemon leaves [ 76 ]. The contents of H 2 O 2 , MDA, proline and the activities of SOD, POD and CAT in Arabidopsis and lemon leaves were detected by corresponding measurement kits (Nanjing Jiancheng Bioengineering Institute, Nanjing, China) according to a previous report [ 77 ]. The ABA contents in Arabidopsis and lemon leaves were measured by enzyme-linked immunosorbent assay (ELISA) according to a previous report [ 78 ].…”
Section: Methodsmentioning
confidence: 99%
“…The article by Liang et al [ 8 ] focuses on the transcriptome and physiological analyses of a navel orange mutant (MT) with improved drought tolerance and water use efficiency (WUE) caused by the increased accumulation of cuticular wax and ROS (Reactive Oxygen Species)—scavenging capacity. The MT was found to produce greater total amounts of waxes and aliphatic wax compounds, including n-alkanes, n-primary alcohols, and n-aldehydes, than the wild-type (WT) plant.…”
mentioning
confidence: 99%